A percepção dos pais e responsáveis sobre o uso da radiação ionizante, proveniente de exames de imagem, utilizada em pacientes pediátricos em um hospital de ensino em Sorocaba, São Paulo - Martins, Fernando Martos (2020)
Introduction: There are many benefits of the ionizing radiation use in the medical field. However, it´s possible deleterious effects are often overlooked and its use may increase the incidence of cancer, especially in the pediatric population. Different initiatives have been taken to reduce the dose of ionizing radiation in these patients. Objectives: To verify the perception of parents and caregivers of pediatric inpatients about the use of ionizing radiation in imaging exams. Materials and methods: This is an exploratory, descriptive and cross-sectional study, which has quantitative and qualitative data. Data collection was carried out through a questionnaire with 17 closed questions and two open questions, completed by 77 parents or responsible of pediatric inpatients admitted to Santa Lucinda’s Hospital, Sorocaba-SP. The analysis of the questions was made using quantitative and qualitative perspectives. Results: Most participants understand the reason for the requested exams, but do not know what ionizing radiation is. There is a pressure made by the parents to the doctors requesting exams. The initiatives to control the use of ionizing radiation in the hospital are being deficient, represented by the distribution of radioprotection card. Conclusion: Parents and caregivers are poorly informed about the risks of ionizing radiation. Educational initiatives that emphasize the doctor-patient relationship can reduce the number of exams that uses ionizing radiation. Also, it’s still important to maintain and properly manage existing proposals for dose reduction